A Psychic Journey to “Somewhere House” in Helen Oyeyemi‟s the Icarus Girl, the Opposite House and White is for Witching - G. , Vetriselvi (International Journal of Psychosocial Rehabilitation, 2020)
My current paper examines the psychic journey to „Somewhere House‟ in the select fictions of Nigerian-born British writer Helen Oyeyemi. She is one of the prominent contemporary female authors. Oyeyemi migrated to Britain when she was young to pursue her education and inhabit the new home. This study focuses on the psychic journey to „Somewhere House‟ undergone by the protagonists in Oyeyemi‟s novels The Icarus Girl, The Opposite House, and White is for Witching. Characters in these novels experience “differences” in connecting attachment to the new home and the spirit world. The occupants in the „Somewhere house‟ were subjected to different identities in terms of fragmentation, disruption, and cultural displacement. My research discusses how the fantastic irruptions of the „Somewhere House‟ are taken into the real world as a discourse on assimilation and cultural deterioration. This research paper foregrounds and drives towards another imaginary world of „Somewhere House‟ with different criteria in the construction of character identity in Oyeyemi‟s novels The Icarus Girl, The Opposite House, and White is for Witching. Her characters are often symbolic representatives of the negotiation of intersecting traumas.